Iatrogenic Cushing’s Syndrome Following Intra-Articular Triamcinolone Injection in an HIV-Infected Patient on Cobicistat Presenting as a Pulmonary Embolism: Case Report and Literature Review - Alidoost M; Conte GA; Agarwal K; Carson MP; Lann D; Marchesani D (International Medical Case Reports Journal, 2020)
Marjan Alidoost, Gabriella A Conte, Khushboo Agarwal, Michael P Carson, Danielle Lann, Diane Marchesani Department of Medicine, Hackensack Meridian Health Jersey Shore University Medical Center, Neptune, NJ 07753, USACorrespondence: Marjan Alidoost Email Marjan.Alidoost@hackensackmeridian.orgBackground: Iatrogenic Cushing’s syndrome (ICS) typically develops after long-term exposure to corticosteroids, but it can occur after a single dose in patients treated with cobicistat or ritonavir for HIV. We present a patient who developed ICS due to the interaction between cobicistat and triamcinolone, a review of the literature, and what to our knowledge is the first case of ICS presenting as a pulmonary embolism.Case Presentation: A 55-year old male with a past medical history of human immunodeficiency virus, undetectable for 15 years and currently on elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide, received 2 intra-articular injections of triamcinolone one month apart for a Baker’s cyst in his right knee. He used nasal fluticasone for 9 days in-between the injections. After his second knee injection, he developed easy bruising and friable skin. Over the coming months, he experienced weight gain and Cushingoid facies. Four months after the knee injections he developed a pulmonary embolism and deep vein thrombosis treated with warfarin. The Cushingoid facies prompted an evaluation and diagnosis of ICS along with hypothalamic pituitary adrenal axis suppression.Conclusion: This case demonstrates the need to monitor patients on pharmacological boosters with any exposure to corticosteroids, whether it be injected, inhaled, topical, oral or intravenous, as it can lead to profound adrenal suppression and ICS.Keywords: human immunodeficiency virus, iatrogenic Cushing’s syndrome, adrenal suppression, case report